Advertising billboard in Asuncion city, and the effects on the urban environment - Ayala Rodríguez, Jessica Jazmín (2020)
The advertising posters in urban sites can become a visual pollutant with varied effects on the environment and people. In this study, the perceived environmental effect of the population in the areas with the most dynamic advertising posters was described. The study is quali-quantitative, non-experimental, transectional and exploratory-descriptive. For the study, two sampling sites were defined on intersections of the main avenues of the capital that showed the greatest number of posters enabled in the 2014-2016 period. At each point, observation was made and the perception of settlers, bystanders, key and qualified informants was included. Some of the negative environmental effects mentioned above were cutting down trees for the placement of posters and affecting the image of the city of Asunción as a sustainable city. It is concluded that the presence of advertising posters can cause environmental damage in the urban environments where it is inserted